ORIENTASI KEBAHAGIAAN SISWA SMA, TINJAUAN PSIKOLOGIINDIGENOUS PADA SISWA LAKI-LAKI DAN PEREMPUAN - Oetami, Putri; Yuniarti, Kwartarini Wahyu (Universitas Ahmad Dahlan, 2011)
The purpose of this study was to analyze the happiness orientation ofboys and girls. A number of 459 high school students in Yogyakarta andCiamis filled out questionnaire with open-ended questions developed byKim and information about the data itself. The analysis method in this studyused a combination of qualitative and quantitative methods with indigenouspsychology approach, an approach from the perspective of the local culture,was used to analyze the data response from open questions, so the originaldata was obtained in the reality of Indonesia itself, so every phenomenonwas seen in context, presented and interpreted in relative terms based onthe cultural, ecological, and where the phenomenon took place.Categorization responses were analyzed by cross tabulation statisticalmethods with the sex of respondents. The results showed that there wasno significant difference in happiness boys and girls. Events that made themost happy for the boys was the event associated with achievement,spirituality, friends, and leisure time, whereas for girls was associated withfamily, love and be loved, as well as money.